Perilaku Remaja Dalam Penggunaan Media Internet Di Nagari Lakitan Kecamatan Lengayang Kabupaten Peissir Selatan - Khairani, Era Zulmi; Erianjoni, Erianjoni; Firdaus, Firdaus (Pendidikan Sosiologi, 2013)
This essay explains about adolescent behaviour using internet media in Lakitan village Lengayang district south pesisir regency. Internet in the school and internetâs stail make adolescent easy to access internet. The function of internetâsÂ  stail as a media to get information, have change to be a place to playing game online, chatting and access the other website, so can influence adolescent behaviour. Based on the problems above, the purpose of this research are: (1) The motivate factor using internet by adolescent in Lakitan village Lengayang district south Pesisir regency, (2) The model of internet that use by adolescent in Lakitan village Lengayang district south Pesisir regency, (3) the impact of use internet by adolescent in Lakitan village Lengayang district south Peissir regency.The theory is Max Weber theory about social action and Edwin Shuterland about deviate attitude. In this research us qualitative approach, to explain strong theory. Informan of this research are twenty five people. The data cinsists of words and action. World and obsevation people and interview are prime source. Thecnique and collecting data too;s are interviewing, observation, documentation and collecting data tools are interview instruction, book, pen, and handhphone.The result of this research shows the motivate factor adolescent use internet in Lakitan village Lengayang district south Pesisir Regency are education factor, are the internet that use by adolescent in Lakitan village Lengayang district south Pesisir regency are communication media like facebook, chatting and to entertain media like game online in internet. The impact of use internet in Lakitan village Lengayang district south Pesisir regency are positive of task and increas adolescent knowledge and negative impact like social deviate attitude that open pornogarfi, less of achievement in the school and always lie to parents in home.